Management Increasing Work Motivation to Adaptation of Work Culture During Work From Home (WFH) at PT. Gemilang Rizky Medika - Sadiqin, Amin (Lafadz Jaya Publisher, 2022)
Working from home can be a very effective behavior for cost efficiency or consumption expenditure and transportation costs that must be issued when working in the office. This should make employees more comfortable and more productive at work. However, in practice there are many problems faced by companies when applying the WFH method, one of which is the lack of increasing employee motivation at work and even decreasing motivation as happened at PT Gemilang Rizky Medika. This study uses a qualitative approach. The data was obtained by interviewing the owner of the company. The results of this study state that the causes of employees of PT Gemilang Rizky Medika losing work motivation when organizational culture changes occur, among others, being unfamiliar with the work system at home, lack of work facilities at home and lack of coordination between teams. The forms of motivation given by the leadership of PT Gemilang Rizky Medika to employees during WFH include: 1) communication between leaders and subordinates must run well; 2) awarding employees; 3) work flexibility that is not too tight and 4) providing supervision and punishment to employees.